1939
DOI: 10.1103/physrev.55.748
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Evaporation of Tantalum

Abstract: The rate of evaporation of tantalum was determined by measuring the change of resistance and the change of weight of uniform filaments. Temperatures were held constant throughout each run by adjustments of voltage V and current A so that VA$ remained approximately unchanged. The rate of evaporation can be expressed by logioM=7.86 -39,310/jf, where M is the rate of evaporation in grams per cm 2 per sec. and T is the temperature on the Kelvin scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1958
1958
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…[27] The data presented for Ta evaporation in Figure 6 are from the measurements performed by Langmuir and Malter [30] at high temperatures and high vacuum conditions and below the melting point of Ta. At very low pressures, higher Ta evaporation rates than the theoretic rates are observed.…”
Section: Evaporation Rate Of Pure Metalsmentioning
confidence: 99%
“…[27] The data presented for Ta evaporation in Figure 6 are from the measurements performed by Langmuir and Malter [30] at high temperatures and high vacuum conditions and below the melting point of Ta. At very low pressures, higher Ta evaporation rates than the theoretic rates are observed.…”
Section: Evaporation Rate Of Pure Metalsmentioning
confidence: 99%
“…This indicated that the silicon melted and evaporated before the Ta could melt. As the vapor pressure of Si ( P v (Si) = 4.07 × 10 6 atm at T = 1623 K [ 14 ]) is higher than that of Ta ( P v (Ta) = 6.66 × 10 −6 atm at T = 3269 K [ 15 ]) and has a much lower melting ( T m (Si) = 1687 K, T m (Ta) = 3293 K [ 5 ]) and boiling ( T b (Si) = 3538 K, T b (Ta) = 5731 K) point, Si was placed at the bottom of the graphite crucible and Ta on top prior to evaporation in the reported experiment ( Figure 5 a).…”
Section: Resultsmentioning
confidence: 99%
“…By the end of the melting phase, the homogeneous Ta-Si liquid will have filled the crucible. During the evaporation phase, the evaporation rates of Ta and Si in the Ta-Si liquid would be expected to be higher and lower, respectively, to some degree compared to pure Ta ( R exap (Ta) = 6.80 × 10 −5 g·cm −2 ·s −1 at T = 3269 K [ 15 ]) and Si ( R exap (Si) = 14.1 × 10 7 g·cm −2 ·s −1 at T = 1623 K [ 14 ]). However, it is still expected that the evaporation rate of Si would still be significantly higher than that of Ta and thus the Si concentration in the vapour would be much higher than that of Ta.…”
Section: Discussionmentioning
confidence: 99%